SOCIAL SUPPORT, STRESS COPING SKILL, AND LIFE SATISFACTION OF MIDDLE-AGED AND ELDERLY ADULTS: A PATH ANALYSIS. (11th November 2018) - LEE, K; Jun, H; Park, H
Abstract: As Korea is experiencing an "aging" society, academic interests in the quality of life in later life has been increasing. Although social support and stress coping skill are considered important to improving the quality of life of adults, only a few studies have empirically examined the relationship among social network, stress coping skill, and life satisfaction. Therefore, this study was conducted to examine the effects that social support has on the life satisfaction of middle-aged and elderly adults through stress coping skill. For the analysis, the 5th wave of the Korean Retirement and Income Study was utilized and the sample was 7, 638 individuals aged 45 and above. Social support was measured by emotional, informational, material, and appraisal supports and stress coping skill was measured using the COPE scale. Life satisfaction was measured using the Satisfaction with the Life scale. Using Stata 13.0, the pathways from social support to life satisfaction of middle-aged and elderly adults through stress coping skill were analyzed. The results indicate that higher levels of social support increased the level of stress coping skill (b=.25, p<.001) and they positively affected life satisfaction (b=.51, p<.001). The indirect effect was also significant that social support was indirectly related to life satisfaction through stress coping skill (b=.35, p<.001). These findings suggest that political interventions are needed for middle-aged and elderly adults to maintain and expand social networks and to establish effective stress coping strategies based on social resources in order to improve the quality of life in later life.